Effect of Tuak Dayak on Testicular Organ Performance: In Vivo Study - Sius, Usu; Elisebath Wahyu Savitri; Rizkie Woro Hastuti (HM Publisher, 2022)
Tuak Dayak is an alcoholic drink that is often consumed by the people of West Kalimantan. Infertility is related to ROS levels as a result of alcohol oxidative stress. This study aims to determine the effect of tuak dayak on the 8-OHdG levels of semen and testicular weight. This research is an experimental study using experimental methods with a post-test-only randomized control group design. The research subjects were 25 rats, randomly divided into 5 groups. Group K0 was only given 3.6 mL/kgBW/day of distilled water, groups K1 and K2 were given Tuak Aren at doses of 1.8 and 3.6 mL/kgBW/day, and groups K3 and K4 were given Tuak Dayak at doses of 1.8 and 3.6 mL/kgBW/day. Treatment for 4 weeks. On day 29, semen and testes were taken. The testes are weighed with an electric weigher. Analysis of semen in the testes was performed to check the levels of 8-OHdG. The results of the Mann-Whitney test on K4 and K3 had no effect on the 8-OHdG content of cement. The average result in K4 was the number of Leydig cells 3.68±0.18, the thickness of the tubular tissue was 2.13±0.14µg, and the testicular weight was 0.91±0.09 g, the lowest. The average 8-OHdG content of cement was 0.22±0.01 ng/mL, the lowest was K2, and the highest was at K0 1.14±0.05 g/mL. In conclusion, Tuak Dayak had the effect of lowering testicular weight but did not show any effect on the activity of 8-hydroxy-2'deoxyguanosine (8-OHdG) in the semen of rats.